A. 2x2 + x
B. 2x2 + 5x
C. 2x2 + 5x + 6
D. 2x2 + x + 6
Answer:
Step-by-step explanation:
Subtract these polynomials.
To subtract, we multiply negative sign inside the second parenthesis
To subtract the polynomials we combine like terms
Step-by-step explanation:
3ax - 4x = 15a - 20
x(3a - 4) = 15a - 20
so,
x × 3a = 15a
x × 3 = 15
x = 15/3 = 5
x × -4 = -20
x = -20/-4 = 5
since both terms have the same solution, it is the solution for the whole equation :
x = 5
2.) 3(4 x - 4) - 7 x
3.) 3(-4 x + 4) - 7 x
4.) -3(-4 x - 4) - 7 x
this is multiple choice
TherightanswerisofoptionB.
please see the attached picture for full solution
Hopeit helps
Goodluck on your assignment
Answer:
2.) 3(4 x - 4) - 7 x
Step-by-step explanation:
b. Find the truth set of 2x-3 +3 = -1
Answer: b. X=-1/2
Step-by-step explanation:
2x-3+3=-1-3 and +3 cancel each other
2x=-1 both sides divided by 2
X=-1/2
Answer:
Step-by-step explanation:
Here, the dividend is
While divisor is x - 1
In the synthetic division,
We will follow the following steps,
Step 1) Write the coefficient of the dividend in the decreasing order of degree,
Hence, the element in the first row under the division sign are 1, 0, 0, 0, - 1
Step 2) By putting x - 1= 0, we get x = 1
Hence, write down 1 outside the sign,
Here the problem is set up correctly, So, bring the leading coefficient (first number) straight down.
Step 3) Multiply the number in the division box with the number that we brought down and put the result in the next column. Then, Add the two numbers together and write the result in the bottom of the row.
Step 4) Repeat the third step until you get the last element ( here the last element is 0,
Thus, We get numbers in the third row, 1, 1, 1, 1 ( Except 0 )
⇒ Quotient is
Answer:
C
Step-by-step explanation: